Class II phosphoinositide 3-kinase C2ß regulates a novel signaling pathway involved in breast cancer progression. - Chikh, A.; Ferro, R.; Abbott, J.; Piñeiro, R.; Buus, R.; Iezzi, M.; Ricci, F.; Bergamaschi, D.; Ostano, P.; Chiorino, G.; Lattanzio, R.; Broggini, M.; et al. (Impact Journals LLC, 2016)
It is now well established that the enzymes phosphoinositide 3-kinases (PI3Ks) have a key role in the development and progression of many cancer types and indeed PI3Ks inhibitors are currently being tested in clinical trials. Although eight distinct PI3K isoforms exist, grouped into three classes, most of the evidence currently available are focused on one specific isoform with very little known about the potential role of the other members of this family in cancer. Here we demonstrate that the class II enzyme PI3K-C2β is overexpressed in several human breast cancer cell lines and in human breast cancer specimens. Our data indicate that PI3K-C2β regulates breast cancer cell growth in vitro and in vivo and that PI3K-C2β expression in breast tissues is correlated with the proliferative status of the tumor. Specifically we show that downregulation of PI3K-C2β in breast cancer cell lines reduces colony formation, induces cell cycle arrest and inhibits tumor growth, in particular in an estrogen-dependent in vivo xenograft. Investigation of the mechanism of the PI3K-C2β-dependent regulation of cell cycle progression and cell growth revealed that PI3K-C2β regulates cyclin B1 protein levels through modulation of microRNA miR-449a levels. Our data further demonstrate that downregulation of PI3K-C2β inhibits breast cancer cell invasion in vitro and breast cancer metastasis in vivo. Consistent with this, PI3K-C2β is highly expressed in lymph-nodes metastases compared to matching primary tumors. These data demonstrate that PI3K-C2β plays a pivotal role in breast cancer progression and in metastasis development. Our data indicate that PI3K-C2β may represent a key molecular switch that regulates a rate-limiting step in breast tumor progression and therefore it may be targeted to limit breast cancer spread.